Kenyamanan, Kepercayaan, Kepuasan Dan Dampaknyaterhadap Loyalitas Konsumen Ms. Glow Di Reseller Zahro Store Singosari KAB. Malang - Anggraeni, Fitri Dwi; Hidayati, Nur; Athia, Ita (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study aims to determine the influence of convenience, trust, and satisfaction and their impact on consumer loyalty toward Ms. Glow at Zahro Store Reseller in Singosari, Malang Regency. Based on Google Trends data, although the Ms. Glow brand shows a higher search interest compared to other brands, a downward trend occurred at the end of the year. Therefore, an in-depth study of consumer loyalty is necessary to identify the factors influencing this decline in interest. The sampling technique used is a saturated sample obtained from 60 consumers. The data collection method used was a questionnaire distributed directly to Zahro Store customers. The data analysis technique employed in this study is multiple linear regression. The results indicate that convenience, trust, and satisfaction simultaneously influence consumer loyalty. Convenience has a partial effect on consumer loyalty, while trust and satisfaction do not have a partial effect on consumer loyalty. Keywords: Comfort, Trust, Satisfaction, Consumer Loyalty